An prediction of structural behavior in high beam based on finite element modeling (FEM) - Fachrul Adly; Muhammad Aswin; Gina Cynthia R. Hasibuan (SEAN Institute, 2024)
An Until now, there are still many reinforced concrete constructions using high beams. High beam planning often uses analytical concepts. In this research, the structural behavior of high beams due to applied loads will be studied based on Finite Element Modeling (FEM) based simulations using Ansys and Abaqus. The structural behavior in question is the relationship between load and deflection. This research activity aims to ensure that FEM can be used optimally to predict the structural behavior of high beams without having to carry out experimental studies. Based on the results of the FEM analysis using Ansys, it shows that the prediction of the high beam load capacity has an error rate of between 1.5-3.77%. Meanwhile, based on the use of Abaqus software, it shows an error rate of 1-2%. Meanwhile, for the predicted value of high beam deflection capacity, the use of Ansys software gives an error value of 2.11-5.12%. Meanwhile, Abaqus software shows an error rate between 0.26-3.32%. The results of FEM analysis based on Ansys and Abaqus provide good accuracy.